2012
DOI: 10.1136/emermed-2011-200586
|View full text |Cite
|
Sign up to set email alerts
|

Delirium within the emergency care setting, occurrence and detection: a systematic review

Abstract: Recent recommendations from the Society for Academic Emergency Medicine and the American College of Emergency Physicians identified the detection of delirium in the emergency department (ED) as a 'high yield' research objective. This review aimed to determine the occurrence rate, and physician detection rates, of delirium within the ED. A systematic literature review was conducted and identified using online databases. Prospective cohort and cross-sectional studies from hospital EDs were interrogated. Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
69
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 50 publications
5
69
0
2
Order By: Relevance
“…23 Dementia and functional dependency are predisposing factors of delirium clearly identified in ED and hospitalized patients, regardless of whether the delirium is prevalent or incident. 4,7 These findings are widely described in prior studies. 8,23,24 Several studies have shown that a high proportion of elderly patients admitted for cardiac decompensation (in particular HF) concomitantly have some geriatric syndrome that worsens their prognosis.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…23 Dementia and functional dependency are predisposing factors of delirium clearly identified in ED and hospitalized patients, regardless of whether the delirium is prevalent or incident. 4,7 These findings are widely described in prior studies. 8,23,24 Several studies have shown that a high proportion of elderly patients admitted for cardiac decompensation (in particular HF) concomitantly have some geriatric syndrome that worsens their prognosis.…”
Section: Discussionsupporting
confidence: 76%
“…10 In studies conducted in ED populations similar to our study cohort, the prevalence delirium ranges from 7% to 15% at admission, although most studies show a prevalence of approximately 10%. 4,5,22 These data suggest the prevalence of delirium could be somewhat higher in patients with decompensated HF than in patients who present to the ED for other reasons. Although studies focusing on this aspect are lacking, the prevalence of delirium in HF is not negligible.…”
Section: Discussionmentioning
confidence: 88%
“…This incidence rate of delirium (14%) reflected international hospital data 14 . It is of concern that delirium was not formally documented in the medical records of the majority of the patients who presented with a delirium (27 of the 31 patients -87%).…”
Section: Discussionsupporting
confidence: 55%
“…(7) Other studies of elderly patients attending the ED reported an even higher frequency of missing the diagnosis of delirium, ranging from 65-84%. (5,8,9) The lower frequency of missed diagnosis found by Elsayem et al could relate to many factors: the delivery of two lectures to their ED physicians on delirium; priming the ED physician in assessing whether the patient could be approached for study recruitment; and exclusion of patients with dementia and those attending between 6pm and 10am. Regardless, missing the diagnosis of delirium in 41% of cases is a serious concern.…”
mentioning
confidence: 98%
“…(5,(8)(9)(10) However, given the higher prevalence figures for delirium in hospitalized cancer patients, (1) the 9% prevalence seems low. Of the study eligible patients (n=624), 47% (n=291) were noted to be unapproachable for a variety of reasons, including the fact that they were "sleeping/tired".…”
mentioning
confidence: 99%